1998
DOI: 10.1074/jbc.273.35.22825
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycans as Adhesive and Anti-invasive Molecules

Abstract: ARH-77 cells do not adhere to type I collagen and readily invade into collagen gels, but following expression of the transmembrane heparan sulfate proteoglycan syndecan-1, they bind collagen and fail to invade. We now show that cells transfected with syndecan-2 or syndecan-4 also bind collagen and are non-invasive. In contrast, cells transfected with the glycosylphosphatidylinositol-anchored proteoglycan glypican-1 do not bind to collagen and remain invasive, even though glypican-and syndecan-expressing cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(142 citation statements)
references
References 59 publications
(44 reference statements)
5
133
0
3
Order By: Relevance
“…Several extracellular matrix proteins, including fibronectin, collagen, thrombospondin, laminin, and tenascin, interact with cell surface proteoglycans and are thought to modulate cell adhesion through this interaction (2,21,33,45,50,82). In the present study, we have shown that vitronectin also supports proteoglycan dependent cell adhesion.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Several extracellular matrix proteins, including fibronectin, collagen, thrombospondin, laminin, and tenascin, interact with cell surface proteoglycans and are thought to modulate cell adhesion through this interaction (2,21,33,45,50,82). In the present study, we have shown that vitronectin also supports proteoglycan dependent cell adhesion.…”
Section: Discussionsupporting
confidence: 57%
“…Syndecans have been shown to mediate adhesion to other matrix molecules including collagen, fibronectin and laminin (21,22,45,82). To determine whether vitronectin is a ligand for syndecan, ARH-77 cells, each transfected with the cDNA for one of the syndecan family members (syndecans-1, -2, -4) or for a glypican-family member (glypican-1) (42,44,45), were used in cell adhesion assays in order to distinguish which class of proteoglycans can mediate adhesion to vitronectin's heparin binding domain. Figure 5 shows that cells expressing either syndecan-1 or -4 could adhere to wells coated with GST-VnHBD.…”
Section: Vitronectin's Basic Domain Mediates Syndecan Dependent Cell mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Among these proteins involved in cell adhesion mechanisms are syndecans, a four-member family of heparan sulphate proteoglycans expressed on adherent and non-adherent cells. 6 Syndecans have been evaluated in tumour progression owing to their function in cell proliferation, cell-cell and cell-matrix adhesion, cell motility and invasiveness. These heparan sulphate proteoglycans are expressed in several cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Syndecan-1 is expressed mainly in epithelial cells, whereas syndecan-2 has been described in mesenchymal cells. 6 Recent evidence indicates that the pattern of syndecan-1 expression is altered in a number of types of carcinomas, and down-or upregulation of syndecan-1 has been associated with progression and a poor prognosis. 7 In prostate cancer, the expression of syndecan-1 has been investigated with contradictory results.…”
Section: Introductionmentioning
confidence: 99%